1981
DOI: 10.1080/00480169.1981.34776
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione peroxidase activity and selenium concentration in bovine blood and liver as indicators of dietary selenium intake

Abstract: The concentration of selenium (Se) in liver, whole blood, erythrocytes and plasma, and the activity of glutathione peroxidase (GSH-px) in erythrocytes and plasma were monitored in calves transferred between low Se and high Se pastures to determine how each test responded to changes in dietary selenium concentration.Liver and plasma Se concentration and plasma GSH-px activity responded more rapidly than Se concentration in blood or erythrocytes and GSH-px activity in erythrocytes to changes in dietary Se intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1
3

Year Published

1990
1990
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 16 publications
4
11
1
3
Order By: Relevance
“…Serum (or plasma) Se concentration also responds more quickly than whole blood Se to changes in dietary Se concentration (Thompson et al 1980(Thompson et al , 1981. In the present study, serum Se concentration remained unchanged from 30 d before the expected calving date and at calving (Table 3), which corresponded to the weeks with the lowest Se intake.…”
Section: Koenig and Beauchemin * Organic Selenium Yeast For Dairy Cowsupporting
confidence: 50%
“…Serum (or plasma) Se concentration also responds more quickly than whole blood Se to changes in dietary Se concentration (Thompson et al 1980(Thompson et al , 1981. In the present study, serum Se concentration remained unchanged from 30 d before the expected calving date and at calving (Table 3), which corresponded to the weeks with the lowest Se intake.…”
Section: Koenig and Beauchemin * Organic Selenium Yeast For Dairy Cowsupporting
confidence: 50%
“…Thus Thompson et al (1981) obtained the correlation coefficient r = 0.97, Koller et al (1984) Zamorski et al (1995), who investigated the relation between selenium concentration and GSH-Px activity in various species, found significant correlations for cattle (r = 0.63), sheep (r = 0.92), swine (r = 1.0), horses (r = 0.81), and humans (r = 0.88). It can therefore be concluded that our findings confirmed the close correlation between selenium concentration and GSH-Px activity in whole blood.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in the rate of change between tissues, in terms of elemental levels or specific enzyme activity, with increases in trace element intakes are well demonstrated with Se in grazing cattle (Thompson et al 1981). For example, when the changes in the Se concentrations in liver, whole blood, erythrocytes and plasma and the activity of glutathione peroxidase (GSH-px) in erythrocytes and plasma were monitored in calves transferred from a pasture containing 23 ug Se/kg DM (deficient) to one containing 93 ug Se/kg DM (adequate) for 24 weeks, different responses were observed (Thompson et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when the changes in the Se concentrations in liver, whole blood, erythrocytes and plasma and the activity of glutathione peroxidase (GSH-px) in erythrocytes and plasma were monitored in calves transferred from a pasture containing 23 ug Se/kg DM (deficient) to one containing 93 ug Se/kg DM (adequate) for 24 weeks, different responses were observed (Thompson et al 1981). The Se concentrations in the liver and plasma, and plasma GSH-px increased and reached a maximum after 12-16 weeks whereas the erythrocyte Se concentration and GSH-px activity were still increasing at 24 weeks.…”
Section: Discussionmentioning
confidence: 99%